Students' Perceptions of Podcasts as Learning Media to Improve Listening and Speaking Skills in English Learning - Maharani, Nabilla; Ismail, Hijril; Hudri, Muhammad (Universitas Pendidikan Ganesha, 2025)
In the era of globalization, mastering the English language has become very important to facilitate access in various aspects of life, including communication. Listening and speaking are fundamental skills in English. Along with the development of technology, podcasts have become a popular learning media among students. This study aims to determine students' perceptions of podcasts as a learning media to improve listening and speaking skills in English learning. This research method is descriptive qualitative with Likert scale questionnaire and interview. The research samples were 5th and 7th semester students majoring in English Education at Universitas Muhammadiyah Mataram. The results showed positive responses from students that podcasts are effective and interesting as learning media. Podcasts not only improve listening skills, but also speaking, such as finding new vocabulary, correct pronunciation, different accents, and increasing confidence in speaking. Podcasts can be a good alternative in learning English in college. In addition to the benefits of podcasts to improve listening and speaking skills, this study also shows some of the respondents' obstacles in using podcasts. For future research needs to explore how podcasts can be effectively integrated into the English curriculum, focusing on developing communication skills, addressing student challenges, and providing adequate pedagogical support.